2016
DOI: 10.1364/ao.55.008951
|View full text |Cite
|
Sign up to set email alerts
|

Determining the refractive index of human hemoglobin solutions by Kramers–Kronig relations with an improved absorption model

Abstract: The real part of the refractive index (RI) of aqueous solutions of human hemoglobin is computed from their absorption spectra in the wavelength range 250 nm-1100 nm using the Kramers-Kronig (KK) relations and the corresponding uncertainty analysis is provided. The strong ultraviolet (UV) and infrared absorbance of the water outside this spectral range were taken into account in a previous study employing KK relations. We improve these results by including the concentration dependence of the water absorbance as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 23 publications
4
35
1
Order By: Relevance
“…An antisymmetric Lorentzian function (Bain & Preston, ), kL,jfalse(νfalse)=Bjπ()Γjfalse/2false(ν0,jνfalse)2+false(Γjfalse/2false)2Γjfalse/2false(ν0,j+νfalse)2+false(Γjfalse/2false)2, is used to model the contribution of each oscillator to the imaginary part of the refractive index, where the parameters of the j th oscillator are the resonant wavenumber ν 0, j , the full width at half maximum Γ j , and the constant B j . The antisymmetric Lorentzian function was chosen because (i) the imaginary part of the refractive index associated with optical transitions is well‐characterized by a Lorentzian line shape and (ii) it satisfies the symmetry requirements of the Kramers‐Kronig relations (Gienger et al, ).…”
Section: The Effective Oscillator Model For a Weakly Absorbing Aqueoumentioning
confidence: 99%
“…An antisymmetric Lorentzian function (Bain & Preston, ), kL,jfalse(νfalse)=Bjπ()Γjfalse/2false(ν0,jνfalse)2+false(Γjfalse/2false)2Γjfalse/2false(ν0,j+νfalse)2+false(Γjfalse/2false)2, is used to model the contribution of each oscillator to the imaginary part of the refractive index, where the parameters of the j th oscillator are the resonant wavenumber ν 0, j , the full width at half maximum Γ j , and the constant B j . The antisymmetric Lorentzian function was chosen because (i) the imaginary part of the refractive index associated with optical transitions is well‐characterized by a Lorentzian line shape and (ii) it satisfies the symmetry requirements of the Kramers‐Kronig relations (Gienger et al, ).…”
Section: The Effective Oscillator Model For a Weakly Absorbing Aqueoumentioning
confidence: 99%
“…Analysis of the dispersion relation in similar studies showed significant differences for oxyhemoglobin and deoxyhemoglobin, related to the difference in the imaginary part of the RI for the 500 to 600 nm region. 4,[45][46][47][48][49][50] There is lack of data for RI of hemoglobin solutions for concentrations close to that in the red blood cells (RBC), especially for the NIR region.…”
Section: Introductionmentioning
confidence: 99%
“…2) to machine precision. But also curves less generic than this Sellmeier equation (see footnote [30]), e. g., the feature-rich spectral RI of the protein complex hemoglobin [26,27] can be represented with errors well below the respective measurement uncertainties using an appropriate grid spacing ∆ y .…”
Section: Representation Of N(λ)mentioning
confidence: 99%